Pasirinkimo sandorių įkainojimo Markovo modelis - Valakevičius, Eimutis (Lietuvos matematikos rinkinys, 2021)
In the article is proposed the algorithm of modeling the dynamics of asset prices by Markov process with continuous time and countable set of states and numerical option pricing.